Peningkatan Keterampilan Tegak Bersambung Menggunakan Metode Drill di SDN Rumpin 01 - Ade Ayu Lestari; Dadang Kurnia; Nur Hikmah (Tematik: Jurnal Penelitian Pendidikan Dasar, 2023)
The purpose of this study was to improve the writing skills of Class III students at SDN Rumpin 01, Bogor Regency, using the Drill method. The research used a case study qualitative approach, with data collected through observations, interviews, and documentation. The results showed that the students experienced difficulty in writing upright concatenated letters, including writing them incorrectly or outside the lines, resulting in untidy handwriting. However, after using the Drill method, the students' ability to write concatenated letters, especially difficult letters such as A and O, improved significantly. The Drill method also helped the students to learn and practice writing upright concatenated letters regularly, which resulted in better writing skills. The study concluded that the Drill method is an effective way to improve students' writing skills. The method can help students to learn and practice writing upright concatenated letters regularly, resulting in better handwriting. The students showed curiosity and enthusiasm in learning to write concatenated letters, which can increase their ability to write well. Overall, the study provides insights into how the Drill method can be used to improve writing skills in elementary school students.